Whatsapp na escola e a lei geral de proteção de dados pessoais (LGPD) - Queiroz, Elma Cristina Pessoa de (2025)
This study, which is part of the Training, Teacher Professionalization and Educational Work line of research, sought to answer the following question: For what purposes is the WhatsApp application used by teachers in state schools in Goiânia, and what are the implications of its use in light of the General Data Protection Law (GDPL)? The general objective was to analyze the purposes and implications of using WhatsApp in the school environment, considering Law No. 13.709/2018, known as the GDPL. The specific objectives were as it follows: to map the regulation of mobile technology, applications, and the internet in Brazil; to characterize WhatsApp as a technological and social tool; to identify situations in which WhatsApp is used in schools and possible implications from the perspective of the GDPL; and to understand how teachers perceive and engage with WhatsApp at school, as well as their knowledge of the GDPL. This is a qualitative study whose methodological design involved the following steps: documentary analysis of statistical and government data pertinent to the topic, such as bills related to mobile technologies and data on the use of the internet and messaging apps like WhatsApp; bibliographic research, which investigated, through national academic events and repositories of public universities in the Midwest region, how teachers perceive the use of WhatsApp in classrooms; and, finally, field research, conducted via an online questionnaire distributed to basic education teachers in the city of Goiânia, state of Goiás, with the aim of examining teaching practices with mobile technologies, data security, and the purposes of their use. The theoretical analysis presents a vision of technology, especially mobile technology, emphasizing people's mobility and the growing need to remain constantly connected due to the widespread use of mobile apps. This trend has contributed to the emergence of what is known as surveillance capitalism, in which human experience is treated as a by-product. The results of the documentary research justify the need to regulate mobile applications used in Brazil, such as WhatsApp, as the application has become a standard means of communication_ including within schools _ yet lacks defined rules governing its use in educational environments. Regulation could therefore establish limits and offer legal support. The bibliographic research, in turn, revealed a small number of studies focusing on the application and the GDPL, despite the widespread use of WhatsApp for communication, information exchanges, and similar purposes in schools. These findings raise the question of how the WhatsApp application is used in other regions of Brazil, since this research was limited to a specific group certain in the Center-West region. Moreover, the field study conducted with teachers confirmed the trends observed in the previous analyses, emphasizing the importance of investigating the uses and purposes of WhatsApp in education—particularly in relation to data and information security. Although this topic does not appear clearly in the documents analyzed, relevant issues are raised that merit further discussion. In conclusion, the findings highlight the need for teachers and school administrators to pay greater attention to the exposure of personal data in basic education schools. In addition to working with underage students, these professionals assume responsibilities when using an instant messaging application that lacks explicit internal or external guidelines to ensure responsible and non-invasive use, as well as clarity regarding the consequences of its use.